Odpowiedzi

2010-03-26T15:11:08+01:00
K=7n /:7
k/7=n
n= k:7

a=k+6/-6
a-6=k
k=a-6

z=7-y/-7
z-7=-y/:(-1)
z-7/-1=y

tyle umiem ale to jest dobrze na 100%
2010-03-26T15:13:46+01:00
A) k = 7n; n
n = 1/7k

b) a = k + 6; k
k = a - 6

c) z = 7 - y; y
y = 7 - z

d) d = a + bc; c
c =( d-a) : b

e) x = 2k + 1; k
k = (x - 1) : 2

f) 2k = 7n + 5; n
n = 2/7 k - 5/7

Pozdrawiam =)
2010-03-26T15:14:12+01:00
A) k = 7n /7
n=k/7

b) a = k + 6 /-6
k=a-6

c) z = 7 - y /-7
-y=z-7 /*(-1)
y=-z+7

d) d = a + bc /b
d/b=a+c /-a
d/b-a=c

e) x = 2k + 1 /2
x/2= k + 1/2 /-1/2
x/2 - 1/2 =k

f) 2k = 7n + 5 /:7
2/7 k = n+ 5/7 /-5/7
2/7 k - 5/7 =n